Angioplasty experience for central venous stenosis in hemodialysis patients: a case series - Nyoman Saka Ranuartha; Danang Himawan Limanto; Ketut Putu Yasa (Indonesian Vascular Access Association (IVAA), 2023)
Objective: To report the treatment of central venous stenosis in hemodialysis patients with endovascular intervention angioplasty. Introduction: Central venous stenosis is a common case in patients with renal failure or end-stage renal disease who have a history of dialysis, which requires vascular access. The currently available techniques for managing central venous stenosis are endovascular intervention with angioplasty and stent placement. Although open surgical treatment has shown durability in the past, it was correlated with significant morbidity. One of the techniques describes the antegrade technique of endovascular intervention. Case description: In this study present 5 cases of central venous stenosis in patients with hemodialysis. In this case series, the patient complained that had a history of swelling in the upper arm unilateral. Diagnostic with catheterization, there was stenosis of the subclavian vein and innominate. This study performed the endovascular management experience with the preferred treatment for central venous stenosis to perform revascularization procedures which is percutaneous transluminal angioplasty (PTA) with balloon angioplasty. Conclusions: Management of central venous stenosis in patients with hemodialysis can be presented effectively and safely using angioplasty which results in low rates of complication and usually has a shorter length of stay post-procedural.